Metformin With or Without Clomiphene Citrate Versus Laparoscopic Ovarian Drilling With or Without Clomiphene Citrate to Treat Patients With Clomiphene Citrate-Resistant Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Sun, Ming-Li; Bai, Wen-Pei; Song, Qing-Kun; Wang, Hui-Ying; Gao, Guo-Lan; Zheng, Liang; Wang, Xing-He (Frontiers in Pharmacology, 2022)
Introduction: Which is optimal to treat clomiphene citrate-resistant polycystic ovary syndrome (CCR-PCOS) with LOD or metformin remains a problem. There are three inconsistent or even contradictory views. Objectives: The present meta-analysis aimed to evaluate the effectiveness and safety of Metformin with or without CC and to compare them with LOD with or without CC (Met/Met-CC vs. LOD/LOD-CC) in women with CCR-PCOS who also have anovulation. Data source: The PubMed, Cochrane, and Embase databases were searched to identify relevant studies reported between Jan 1, 1966 and Aug 31, 2019; the search was updated on May 17, 2022. Study eligibility criteria: We included randomized controlled trials (RCTs) of CCR-PCOS that had considered Met/Met-CC and LOD/LOD-CC as the exposure variables and fertility as the main outcome variable. Study appraisal and synthesis methods: We assessed study quality using the Cochrane risk-of-bias tool. The primary effectiveness outcome was live birth/ongoing pregnancy rate and the primary safety outcome was miscarriage rate. A fixed-effect meta-analysis was performed. The robustness of the results was assessed using sensitivity analyses. Meta-regression and subgroup analysis were performed to examine the reasons for heterogeneity. Publication bias was examined using the funnel plot, Egger linear regression, and Begg rank correlation tests. The quality of this meta-analysis was estimated according to the GRADE approach. Results: Among 71 potentially relevant studies, we included five RCTs in our meta-analysis. We found no difference in effectiveness between Met-CC and LOD in terms of live birth/ongoing pregnancy (RR=1.02, 95% CI: 0.87–1.21, z=0.28; p=0.780), and miscarriage rates (RR=0.79, 95% CI: 0.46–1.36, z=0.86; p=0.390). I2 tests results revealed moderate or no heterogeneity (I2=51.4%, p=0.083; I2=0.0%; p=0.952). Sensitivity analysis confirmed the robustness of the results. Funnel plot, Egger linear regression, and Begg rank correlation tests implied no publication bias (p>0.05). LOD was more expensive than Met (€1050 vs. €50.16). The evidence quality was moderate. Conclusions: There is no evidence on the difference in the outcomes between the two interventions regarding ovulation, pregnancy, and live birth. As LOD is an invasive procedure and carries inherent risks, the use of Met/Met-CC should be the second-line treatment for women with CCR-PCOS.